(untitled) (International Journal of Engineering and Computer Science, 2018)
One of the major functions of a wireless sensor network is the monitoring of a particular area. Coverage is considered as an important measure of quality of service provided by a wireless sensor network and also emergence of holes in the area of interest is unavoidable due to the nature of WSN nodes. If there is a hole in the network, during data transmission across the hole, the data will move along the hole boundary nodes again and again. This will cause the depletion of energy of nodes in the hole boundary nodes. So detection and healing of such coverage holes is an important factor of concern. Here a hole detection and healing technique based on the energy of nodes is described. Energy based EBHEAL has two phases, Hole detection phase and Hole healing phase. Hole detection phase will detect the existence of hole in the network and its characteristics. Hole healing phase make use of these characteristics to heal the hole. Energy of the nodes are considered to improve the efficiency of the hole healing phase.